Early thromboembolic complications after total cavopulmonary connection/Fontan operation in children: A five year single centre review. (December 2021) - Singh, Davinder; Jerrom, Tom; Issitt, Richard; Saxena, Rohit
Abstract: Background: Patients following total cavopulmonary connection (TCPC)/Fontan surgery are at a higher risk of developing systemic and non-systemic thromboembolic complications (TEC). Despite their potential for being serious and life threatening, very few studies have investigated TEC profile in the early postoperative period in children. Objectives: To study the incidence, symptom profile, possible risk factors, and outcomes in the early postoperative period for up to 12 months following the TCPC/Fontan surgery. Methods: We conducted a retrospective case note review of all children undergoing TCPC/Fontan procedure during a five year period (2014–2018) at our hospital. Electronic case notes and outpatient clinic letters of all identified children were reviewed till 12 months after the date of their TCPC/Fontan surgery. Results: Four out of 96 children (4.2%) developed TEC over the study period - three of them within 2 weeks of surgery. Symptoms ranged from hemiparesis, low cardiac output, and limb pain with swelling. No risk factors could be identified which significantly increase the hazard risk for the development of TEC. There was no significant difference in the incidence of TEC between children initiated on standard or targeted heparin therapy postoperatively in the cardiac ICU. Conclusion: TEC are not uncommon and can present with serious or life threatening symptoms. Due to lack of robust pediatric evidence, there is an urgent need for coordinated, multi-center long term longitudinal follow up research for determining best clinical practice for prevention, surveillance, diagnosis, and treatment of this potentially life threatening complication. Highlights: Early Thromboembolic complications (TEC) after Fontan surgery are not uncommon TEC can present with serious or life threatening/changing manifestations such as stroke No consistent risk factors for TEC can be identified High index of suspicion followed by investigations remains the most effective way to diagnose TEC Routine surveillance for TEC in asymptomatic patients necessitate evidence for clinical and cost effectiveness